Enhancing Vegetative Growth and Nutrient Assimilation Through Nano-Biofertilizers - Jourabchian, Samaneh; Farshchian, Ahmadreza; Shams, Zohreh; Asgharzahed, Maryam (Universitas Brawijaya, 2023)
This study, conducted at Zabol University in Iran during 2019-2020, aimed to investigate the effects of drought stress and various fertilizer treatments on the growth, nutrient assimilation, and essential oil production of rosemary (Rosmarinus officinalis L.). The second year of the experiment yielded the most favorable growth results, attributed to the establishment of mature root systems. Drought stress negatively impacted growth parameters, but the application of nano-bio-fertilizers and bio-fertilizers mitigated these adverse effects. Under drought stress conditions, there was a decrease in leaf nitrogen and phosphorus levels, while potassium levels increased. The utilization of biological and nano-biological fertilizers enhanced the nutritional environment, stimulating root growth and improving soil conditions. Intriguingly, drought stress led to an increase in the production of secondary metabolites, including essential oil. Both nano-systemic and biological fertilizers further augmented essential oil yield, demonstrating their efficacy in high-stress conditions. Additionally, this research identified a negative correlation between plant growth and essential oil percentage. The strategic application of fertilizers has the potential to counteract the detrimental impacts of drought stress, optimizing rosemary's growth and essential oil yield.